Optimization of process parameters for fish oil extraction using atlantic salmon (Salmo salar) frames - Lota, Pamela Joy P.; Dognidon, Kenneth Andrew R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018.)
Fish oil was extracted from Atlantic salmon frames using the wet reduction method. The process time and temperature utilized during extraction was optimized using response surface methodology with a central composite design. The responses measured were the peroxide and acid value of the fish oil extracted. A first degree and a reduced quadratic surface model were obtained for peroxide and acid value, respectively. It was observed that process temperature has statistically significant effects on the peroxide and acid value of the fish oil. Then, in validating the optimal process parameters of 30 minutes and 90.56ᵒC, it was determined that the model produced is capable of predicting responses accurately. Then, the fish oil extracted using the optimal process parameters was characterized. It was determined to have an oil yield of 11.35%, color values of 47.9278 (0.0643), 32.2044 (0.0946), and 68.1011(0.7017) for L*, a*, and b*, respectively, peroxide, thiobarbituric, and acid value of 3.3367 (1.0833) meq O2/kg, 0.2983 (0.0156), and 2.9765 (0.1459) mg KOH/g, respectively, and fatty acid profile mostly consisting of stearic, oleic, and palimitc, at 44.46%, 21.21%, 15.27%, respectively. Given this, the peroxide, acid, and thiobarbituric acid values measured were low, thus suggesting the minimal oxidative and hydrolytic deterioration in the oil during extraction. The results also show that the oil is dark red-yellow in color, while the fatty acid profile revealed that the oil consist mostly of saturated fatty acids. xviii Compared with the standards established by the Codex Alimentarius Commission, the peroxide and acid value obtained were within the acceptable limits. However, the fatty acid composition of the fish oil did not adequately meet the standards. Given this, the fish oil extracted using the optimal process parameters has a potential to be used in applications not intended for human consumption.
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Keywords: Atlantic salmon; Fish oil extraction; Atlantic salmon frames